Students' involvement in physical activity: socio-psychological aspect - Leyfa A.V.; Pavlova E.V.; Strunin I.A.; Romanov V.P. (Theory and Practice of Physical Culture, 2025)
Abstract Objective of the study was to justification of the relevance of the concept of «resource of engagement» in the context of students' physical activity and the comprehensive feature of «resource of engagement in physical activity». Methods and structure of the study. The research sample included 651 full-time students participating in university sports teams, with 353 from Amur State University, 145 from Kurgan State University, and 153 from M.E. Evseviev Mordovian State Pedagogical University. The sample consisted of 36,9% males and 63,1% females. The study was conducted in the spring of 2024. To analyze the interrelationships between the individual components of the «engagement resource», factor analysis was employed. The method of factor allocation was the method of the main components, and the rotation method was varimax with Kaiser normalization. Results and conclusions. The article explores the concept of physical activity and its significance in human life. It highlights the significance of studying the participation of young students in physical activities. The article takes a multidisciplinary approach to examining various aspects of engagement. It is noted that the concept of «participation in physical activity» is still evolving. The article argues that the psychological aspect of this concept can be understood through the lens of the «resource of participation in physical activity». The article empirically identifies the psychological dimensions of this resource, which shape the unique characteristics and circumstances of its implementation.